PROFESSIONAL COMMITMENT AND AUDITOR EXPERIENCES ON AUDITORS’S BEHAVIOR IN AN AUDIT CONFLICT SITUATION AND IMPACT ON THE IMPLEMENTATION OF AUDITORS PROFESSION ETHICS - Nurwulan, Liza Laila; Nissa Fasha, Nadya Cipta (Fakultas Pendidikan Ekonomi dan Bisnis, 2018)
This study attempts to assess the impact of professional commitment, experience of the audit, the auditors behavior conflict and ethicts audit profession senior auditors on the auditors and colleagues who worked on the public accountant in Bandung. The research population auditors who worked on the public accountant in Bandung, a total of 24 samples Obtained by purposive sampling method. The research using analysis lane. The results of the testing of hypotheses shows that the commitment of professional and experience the audit for the application of auditors of ethical behavior, professional and audit experience the audit for the application of auditors ethical behavior of professionals through auditors the audit of conflict Obtained by the determination of the 73, 8%. Testing professional commitment and auditing experience is a significant relation. To Significantly Affect not commit professional auditors to conduct the audit of conflict. Experience of audit there are significant impact on the behavior of auditors auditing conflict. For testing of professional commitment, there are significant impact on the audit professional ethics. Experience of audit there are significant impact on the audit professional ethics. Behavior auditors and the audit there are significant impact on the application of professional ethics of auditors.